Flocculation-flotation harvesting mechanism of Dunaliella salina: From nanoscale interpretation to industrial optimization. (15th May 2019) - Besson, Alexandre; Formosa-Dague, Cécile; Guiraud, Pascal
Abstract: Dunaliella salina is a green microalgae species industrially exploited for its capacity to produce important amounts of carotenoid pigments. However in low nitrogen conditions in which they produce these pigments, their concentration is low, which results in harvesting difficulties and high costs. In this work, we propose a new solution to efficiently harvest D. salina at the pre-industrial scale, using flocculation/flotation harvesting induced by NaOH addition in the medium. We first show, using numerical simulations and nanoscale atomic force spectroscopy experiments, that sweeping mechanism in formed magnesium hydroxide precipitate is only responsible for D. salina flocculation in hypersaline culture medium upon NaOH addition. Based on this understanding of the flocculation mechanism, we then evaluate the influence of several parameters related to NaOH mixing and magnesium hydroxide precipitation and show that NaOH concentration, mixing, and salinity of the medium can be optimized to achieve high flocculation/flotation harvesting efficiencies in laboratory-scale experiments. We finally successfully scale-up the data obtained at lab-scale to a continuous pre-industrial flotation pilot, and achieve up to 80% of cell recovery. This interdisciplinary study thus provides original results, from the nano to the pre-industrial scale, which allow the successful development of an efficient large-scale D. salina harvesting process. We thus anticipate our results to be the starting point for further optimization and industrial use of this flocculation/flotation harvesting technique. Graphical abstract: Image 1 Highlights: Only sweeping mechanism is involved in D. salina NaOH-induced flocculation. Mixing of NaOH and Mg(OH)2 precipitation speed are keys for efficient flocculation. Agitation and salinity influence harvesting efficiency by flocculation/flotation. The NaOH injection system is determinant for D. salina high-scale harvesting.